Interprofessional education in the clinical setting: A qualitative look at the preceptor's perspective in training advanced practice nursing students. (November 2016) - Chen, Angel K.; Rivera, Josette; Rotter, Nicole; Green, Emily; Kools, Susan
Abstract: With the shift towards interprofessional education to promote collaborative practice, clinical preceptors are increasingly working with trainees from various professions to provide patient care. It is unclear whether and how preceptors modify their existing precepting approach when working with trainees from other professions. There is little information on strategies for this type of precepting, and how preceptors may foster or impede interprofessional collaboration. The purpose of this qualitative description pilot study was to identify current methods preceptors use to teach trainees from other professions in the clinical setting, particularly advanced practice nursing and medical trainees, and to identify factors that support or impede this type of precepting. Data collected through observations and interviews were analyzed by the research team using thematic analysis procedures. Three major themes were identified: 1) a variety of teaching approaches and levels of engagement with trainees of different professions, 2) preceptor knowledge gaps related to curricula, goals, and scope of practice of trainees from other professions, and 3) administrative, structural and logistical elements that impact the success of precepting trainees from different professions in the clinical setting. This study has implications for faculty development and evaluation of current precepting practices in clinical settings.